A UV cross-linked water-based exposed roof waterproof coating and its preparation and application

By using ultraviolet crosslinked water-based roof exposed waterproof coating, the problems of high requirements for the base surface and complex construction in the prior art are solved, and the self-leveling, flexibility and high adhesion of the coating are achieved. It is suitable for roofs of different substrates and meets strict water resistance and aging performance tests.

CN119463604BActive Publication Date: 2025-04-15FOSHAN MERLIN COATING
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510070501.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing exposed roof waterproof coatings have high requirements for the base surface. During construction, the base surface must be flat, strong, clean, without hollowing or cracks. The wire mesh must be laid after the first coat of paint. Otherwise, there will be problems such as bulging, easy to lift, and poor adhesion, which will increase the construction process and material costs.

Method used

UV crosslinked water-based roof exposed waterproof coating is used, and its components include multifunctional additives, ammonium salt dispersants, film forming additives, substrate wetting agents, defoaming agents, thickening agents, heavy calcium powder, titanium dioxide, acrylic elastic emulsions and styrene acrylic emulsions, etc. Through specific ratios and process steps, a prereaction slurry with a fineness of 30 to 40 microns is formed, which improves the self-leveling, flexibility and adhesion of the coating.

Benefits of technology

The coating can automatically level and fill cracks of ≤1mm without laying wire mesh. It is suitable for roofs of different substrates. It has excellent flexibility, adhesion and water resistance, and meets 5000h artificial climate aging performance test, 720h water resistance test and 168h water impermeability test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463604B_ABST
    Figure CN119463604B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and discloses a UV cross-linked water-based exposed roof waterproof coating and its preparation and application. The components of the waterproof coating are as follows by weight: 1 to 5 parts of multifunctional auxiliary agent, 5 to 10 parts of ammonium salt dispersant, 5 to 10 parts of film-forming auxiliary agent, 2 to 6 parts of substrate wetting agent, 1 to 5 parts of mineral oil defoamer, 1 to 5 parts of organosilicon defoamer, 1 to 5 parts of alkali swelling thickener, 1 to 5 parts of polyurethane thickener, 300 to 400 parts of heavy calcium powder-coarse powder, 50 to 150 parts of heavy calcium powder-fine powder, 1 to 20 parts of titanium dioxide, 350 to 450 parts of acrylic elastic emulsion, 80 to 120 parts of styrene-acrylic emulsion, and 55 to 125 parts of deionized water; the acrylic elastic emulsion has a solid content of 52±1%, a viscosity of ≤500 mPa·s, a glass transition temperature of ‑18°C, a minimum film-forming temperature of 0°C, and a density of 1.04 g / cm 3 The waterproof coating of the present invention has excellent bonding strength, self-leveling performance, waterproof air overflow performance and flexibility, has long-lasting waterproof and weather-resistant performance, and meets the requirements of outdoor applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an ultraviolet cross-linked water-based exposed roof waterproof coating and a preparation method and application thereof. Background Art

[0002] Exposed roof waterproof coating is a kind of waterproof material that can be directly exposed to the external environment. At present, the common exposed roof waterproof coatings are mainly the following: 1) Acrylate multipolymer coating: This is a water-based waterproof coating with acrylate multipolymer emulsion as the main raw material, suitable for metal roofs, concrete roofs, asphalt roofs, etc. For example, a Chinese invention patent with publication number CN105368236A discloses a waterproof coating, a preparation method and application thereof, and an asphalt waterproof membrane, wherein the waterproof coating comprises 50-70 parts of a polymer emulsion, 30-50 parts of a filler, 1-5 parts of a liquid petroleum resin, 0.2-0.5 parts of a coupling agent, 0.2-0.4 parts of a dispersant, 0.1-0.2 parts of a wetting agent, 0.5-1.5 parts of a film-forming aid, 0.3-0.7 parts of a thickener, 0.2-0.7 parts of a defoaming agent, and 5-10 parts of water; the polymer emulsion comprises one or a mixture of several of a polyacrylate emulsion, a styrene-acrylate copolymer emulsion, a vinyl acetate-acrylate copolymer emulsion, and a silicone-acrylate copolymer emulsion.

[0003] 2) Styrene-acrylic paint: It is made of styrene-acrylic emulsion and acrylic emulsion as the main raw materials, and is added with a variety of additives and fillers. It is suitable for renovation of old roofs. For example, a Chinese invention patent application with publication number CN103992698A discloses a waterproof elastic exterior wall paint, which is composed of the following components by weight: 100 parts of styrene-acrylic emulsion, 35-40 parts of styrene emulsion, 7-9 parts of acrylic emulsion, 6-10 parts of hydroxyethyl cellulose, 5-8 parts of dispersant, 0.8-1.6 parts of defoamer, 12-16 parts of ethylene glycol, 0.5-1.5 parts of preservative, 1-2 parts of wetting agent, 40-50 parts of titanium dioxide, 35-45 parts of light calcium carbonate, 20-24 parts of talc, 33-35 parts of kaolin, 0.3-0.7 parts of leveling agent, and 70-76 parts of water.

[0004] Although the existing exposed roof waterproof coatings can be applied to roofs of different substrates and have good adhesion and bonding, they have high requirements on the base surface. During construction, the base surface must be flat, solid, clean, without hollows or cracks. If there are cracks, they must be filled with a specific base filler. In addition, the silk screen must be laid after the first coat of waterproof coating is applied. Otherwise, it is very easy to have bulging, easy to lift up, and poor bonding after the construction is completed, which undoubtedly increases the construction process and material costs. Summary of the invention

[0005] The purpose of the present invention is to provide a UV-crosslinked water-based exposed roof waterproof coating with better self-leveling performance, flexibility and adhesion, and its preparation and application, in order to solve one or more technical problems existing in the prior art and at least provide a beneficial solution or option.

[0006] To achieve the above objectives, the present invention adopts the following technical solutions.

[0007] A UV cross-linked water-based exposed roof waterproof coating, the components of which are as follows by weight: 1-5 parts of a multifunctional auxiliary agent, 5-10 parts of an ammonium salt dispersant, 5-10 parts of a film-forming auxiliary agent, 2-6 parts of a substrate wetting agent, 1-5 parts of a mineral oil defoamer, 1-5 parts of an organosilicon defoamer, 1-5 parts of an alkali swelling thickener, 1-5 parts of a polyurethane thickener, 300-400 parts of heavy calcium powder-coarse powder, 50-150 parts of heavy calcium powder-fine powder, 1-20 parts of titanium dioxide, 350-450 parts of an acrylic elastic emulsion, 80-120 parts of a styrene-acrylic emulsion, and 55-125 parts of deionized water.

[0008] The preparation steps of the above-mentioned UV cross-linked water-based exposed roof waterproof coating are as follows.

[0009] 1) Place 50-100 parts of deionized water, 1-5 parts of mineral oil defoamer, 1-5 parts of multifunctional additive, 5-10 parts of ammonium salt dispersant, 100-150 parts of acrylic elastic emulsion, 300-400 parts of heavy calcium powder-coarse powder, 50-150 parts of heavy calcium powder-fine powder, and 1-20 parts of titanium dioxide in a disperser, disperse and mix them at a high speed of 1000-2000 r / min at room temperature to obtain a pre-reaction slurry 1 with a fineness of 30-40 microns.

[0010] 2) Add 250-300 parts of acrylic elastic emulsion, 80-120 parts of styrene acrylic emulsion, 5-10 parts of film-forming aid, 2-6 parts of substrate wetting agent and 1-5 parts of silicone defoaming agent to the pre-reaction slurry obtained in step 1), disperse and mix evenly at a speed of 800-1200 r / min at room temperature to obtain pre-reaction slurry 2.

[0011] 3) Premix 1-5 parts of alkali swelling thickener and 2-10 parts of deionized water and stir them evenly for later use; premix 1-5 parts of polyurethane thickener and 3-15 parts of deionized water and stir them evenly for later use; add the premixed alkali swelling thickener and polyurethane thickener to the pre-reaction slurry 2 obtained in step 2) to keep the viscosity of the whole system at 120-140ku, and obtain a UV cross-linked water-based roof exposed waterproof coating.

[0012] When applying, use a roller to apply a layer of waterproof coating on a clean, flat, hollow-free concrete or metal base surface. Wait for 4 to 12 hours until the surface is dry and not sticky, then check for hollowing, bubbling, delamination, and poor curing. If these problems occur, repair them and then apply a second layer of coating. The second coating direction is perpendicular to the first coating direction, and the coating thickness of each layer is controlled at 0.3mm-0.5mm.

[0013] In the present invention, 350-450 parts of acrylic elastic emulsion and 80-120 parts of styrene acrylic emulsion are mixed to ensure the tensile strength, elongation at break and low-temperature bendability of the system; at the same time, 1-5 parts of alkali swelling thickener and 1-5 parts of polyurethane thickener are mixed to increase the viscosity of the system and promote the leveling and self-leveling of the system during film formation, so that cracks in the building can still be filled and penetrated, and even the effect of heat insulation can be achieved, and excellent bonding strength and water resistance can be ensured under high elastic properties.

[0014] More preferably, the acrylic elastic emulsion has a solid content of 52±1%, a viscosity of ≤500 mPa·s, a glass transition temperature of -18°C, a minimum film-forming temperature of 0°C and a density of 1.04 g / cm 3 Acrylic elastic emulsion, such as Wanhua Chemical 8015A acrylic elastic emulsion, etc.

[0015] More preferably, the multifunctional additive is selected from AMP95 multifunctional additive sold by Dow Chemical (China) Investment Co., Ltd.

[0016] In the present invention, 1 to 5 parts of a multifunctional additive are added to adjust the pH value of the entire system, making the system alkaline, inhibiting the growth of bacterial flora, and reducing or even eliminating the need to add preservatives and mildew inhibitors. When ≥10 parts of the multifunctional additive are added, the pH value of the system is high, and the alkalinity is enhanced, which will lead to poor stability and the paint sample will not be preserved for a long time; in addition, a pungent odor will be generated, affecting the customer experience. When ≤0.1 parts of the multifunctional additive are added, the pH value of the system does not meet the requirements and may even be acidic, producing an acidic odor that is unpleasant; the pH value does not meet the requirements for inhibiting the growth of bacterial flora, and additional preservatives and mildew inhibitors need to be added, increasing the risk of customer allergies.

[0017] More preferably, the ammonium salt dispersant is selected from the aqueous dispersant sold by Deqian (Shanghai) Chemical Co., Ltd. with model number FX-365.

[0018] In the present invention, adding 5 to 10 parts of ammonium salt dispersant can ensure that the paint sample does not agglomerate or settle during high-speed dispersion, the mixing is more uniform, and the waterproof performance of the system can be improved; if a sodium salt dispersant is added, the waterproof performance of the system will be affected.

[0019] More preferably, the film-forming aid is selected from the film-forming aid model HB-285 sold by Foshan Abel Chemical Co., Ltd.

[0020] In the present invention, 5 to 10 parts of film-forming aid are added to enable the system to form a film better at high or low temperatures, and the film formation will not be too fast or too slow. If ≥ 20 parts of film-forming aid are added, the film-forming speed of the system is too fast and the paint film is prone to cracking; if ≤ 1 part of film-forming aid is added, the film-forming speed of the system is too slow and it is easily affected by the weather or increases the difficulty of construction.

[0021] More preferably, the substrate wetting agent is selected from the substrate wetting agent model SWA-1 sold by Dow Chemical (China) Investment Co., Ltd.

[0022] In the present invention, 2 to 6 parts of the substrate wetting agent are added to enhance the adhesion of the system to the substrate (≥2Mpa), and can also adjust the leveling effect of the paint sample to make the paint film smooth.

[0023] More preferably, the mineral oil defoamer is selected from the mineral oil defoamer model SX-NXZ2 sold by Yangzhou Sixin New Material Technology Co., Ltd., and the silicone defoamer is selected from the silicone defoamer model SX-63A sold by Yangzhou Sixin New Material Technology Co., Ltd.

[0024] More preferably, the alkali swelling thickener is selected from the thickener model A401 sold by Wanhua Chemical Group Co., Ltd., and the polyurethane thickener is selected from the thickener model U604 sold by Wanhua Chemical Group Co., Ltd.

[0025] More preferably, the particle size of the heavy calcium powder-coarse powder is 400-800 mesh, and the particle size of the heavy calcium powder-fine powder is 1000-1250 mesh.

[0026] In the present invention, 300-400 parts of heavy calcium powder-coarse powder and 50-150 parts of heavy calcium powder-fine powder are mixed, which can not only fill the problem of tiny gaps in the paint film caused by using only heavy calcium powder-coarse powder and insufficient density of the system, thereby ensuring the hiding power and waterproofness of the system; but also avoid the problem that the paint film is too dense when using only heavy calcium powder-fine powder, which makes it difficult for water vapor to overflow during construction on a roof with high temperature in summer, resulting in bubbling and hollowing; thereby ensuring the waterproof and air overflow effect of the system.

[0027] The present invention adopts the above technical solution to have at least the following beneficial effects.

[0028] 1. According to actual production verification, the UV cross-linked water-based exposed roof waterproof coating developed by the present invention can automatically level and fill cracks with a spacing of ≤1mm, has low requirements on the base surface and does not require the laying of silk screen to prevent bulging; at the same time, the coating is not only suitable for roofs of different substrates, internal and external facades, covering the performance of ordinary internal and external wall coatings, but also suitable for materials such as paper and cloth, with excellent flexibility and the ability to cover surface cracks; in addition, the coating is also suitable for roads stepped on by many people, without bubbling or falling off, and has excellent adhesion and bonding.

[0029] 2. After actual testing, the UV-crosslinked water-based exposed roof waterproof coating prepared by the present invention meets the 5000h artificial weathering aging resistance test, the 720h water resistance test and the 168h impermeability test. The coating film has no cracks, stratification, bubbles or breakage within 720h, and the coating film is impermeable and leak-free under 0.3Mpa within 168h; the surface has excellent water and weather resistance, and can be used for waterproofing of building exterior walls or waterproofing of roofs, metal plates and glass plates, and does not change color, fall off, crack, delaminate, bubble, stick or have holes under long-term outdoor exposure.

[0030] 3. The UV cross-linked water-based exposed roof waterproof coating prepared by the present invention has a rubber-like feel after film formation, good elasticity, tear resistance, good ductility, and excellent touch when stepped on.

[0031] 4. The UV cross-linked water-based exposed roof waterproof coating prepared by the present invention has low formaldehyde (test content is 0.04 mg / kg), low volatile organic compound (VOC content test is 0.02 g / L), no radioactivity, and the system is green, environmentally friendly and healthy. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0033] Figure 1 Shown is a photograph of an A4 paper after the exposed waterproof coating prepared in Example 1 was applied and a funnel-shaped water seepage test was performed.

[0034] Figure 2 Shown is a photograph of an A4 paper after the exposed waterproof coating prepared in Comparative Example 3 was applied and a funnel-shaped water seepage test was performed.

[0035] Figure 3 Shown is a photograph of the exposed waterproof coating prepared in Example 1 of the present invention being brushed on a road surface and subjected to a trampled accelerated aging test (two years).

[0036] Figure 4Shown is a photograph of the exposed waterproof coating prepared in Comparative Example 4 after being applied to the road surface for an accelerated aging test (two years). DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to better understand the essence of the present invention, the specific implementation methods of the present invention are described in detail below with reference to the accompanying drawings. Example 1

[0038] A UV cross-linked water-based exposed roof waterproof coating, the components of which are as follows by weight: 3 parts of multifunctional additives, 8 parts of ammonium salt dispersants, 8 parts of film-forming additives, 5 parts of substrate wetting agents, 3 parts of mineral oil defoamers, 3 parts of organosilicon defoamers, 4 parts of alkali swelling thickeners, 3 parts of polyurethane thickeners, 350 parts of heavy calcium powder-coarse powder, 100 parts of heavy calcium powder-fine powder, 10 parts of titanium dioxide, 400 parts of acrylic elastic emulsions, 100 parts of styrene acrylic emulsions, and 80 parts of deionized water.

[0039] In the above-mentioned UV cross-linked water-based exposed roof waterproof coating, all the additives are commercially available, among which the multifunctional additive is AMP95 multifunctional additive sold by Dow Chemical (China) Investment Co., Ltd., the ammonium salt dispersant is an ammonium salt dispersant with model number FX-665 sold by Deqian (Shanghai) Chemical Co., Ltd., the film-forming additive is a film-forming additive with model number HB-285 sold by Foshan Abel Chemical Co., Ltd., the substrate wetting agent is a wetting agent with model number SWA-1 sold by Dow Chemical (China) Investment Co., Ltd., the mineral oil defoamer is a defoamer with model number SX-NXZ2 sold by Yangzhou Sixin New Materials Technology Co., Ltd., the silicone defoamer is a defoamer with model number SX-63A sold by Yangzhou Sixin New Materials Technology Co., Ltd., the alkali swelling thickener is a thickener with model number A401 sold by Wanhua Chemical Group Co., Ltd., and the polyurethane thickener is a thickener with model number U604 sold by Wanhua Chemical Group Co., Ltd.

[0040] In the above-mentioned UV cross-linked water-based exposed roof waterproof coating, the acrylic elastic emulsion has a solid content of 52±1%, a viscosity of ≤500 mPa·s, a glass transition temperature of -18°C, a minimum film-forming temperature of 0°C and a density of 1.04 g / cm 3 Acrylic elastic emulsion, such as Wanhua Chemical 8015A acrylic elastic emulsion, etc.

[0041] In the above-mentioned UV cross-linked water-based exposed roof waterproof coating, the particle size of the heavy calcium powder-coarse powder is 600 mesh, and the particle size range of the heavy calcium powder-fine powder is 1100 mesh.

[0042] Obviously, those skilled in the art may also select existing known or future achievable additives with the same properties to replace one or more of the above additives based on the conception principle of the present invention, which is not limited to this embodiment.

[0043] This embodiment provides a UV cross-linked water-based exposed roof waterproof coating, and its preparation steps are as follows.

[0044] 1) Disperse 70 parts of deionized water, 3 parts of mineral oil defoamer, 3 parts of multifunctional additive, 8 parts of ammonium salt dispersant, 350 parts of heavy calcium powder-coarse powder, 100 parts of heavy calcium powder-fine powder, 10 parts of titanium dioxide and 150 parts of acrylic elastic emulsion at high speed in a disperser at room temperature, mix well, and obtain a pre-reaction slurry 1 with a fineness of 30-40 microns.

[0045] 2) Add 100 parts of styrene-acrylic emulsion, 8 parts of film-forming aid, 5 parts of substrate wetting agent, 3 parts of silicone defoamer and 250 parts of acrylic elastic emulsion to the pre-reaction slurry 1 obtained in step 1), and disperse and mix them evenly with a disperser at room temperature to obtain pre-reaction slurry 2.

[0046] 3) Premix 4 parts of alkali swelling thickener and 5 parts of deionized water, stir evenly and set aside; premix 3 parts of polyurethane thickener and 5 parts of deionized water, stir evenly and set aside; add the premixed alkali swelling thickener and polyurethane thickener to the pre-reaction slurry 2 obtained in step 2) to obtain a UV cross-linked water-based roof exposed waterproof coating.

[0047] When applying, first use a roller to apply a layer of waterproof coating on a clean, flat, hollow concrete or metal base surface. Wait for 4 to 12 hours until the surface is dry and not sticky, then check for hollowing, bubbling, stratification, and poor curing. If these problems occur, repair them and apply a second layer of waterproof coating. The second coating direction is perpendicular to the first coating direction, and the thickness of each coating is controlled at 0.3mm-0.5mm.

[0048] The performance test of a UV cross-linked water-based exposed roof waterproof coating prepared in this embodiment is shown in Table 1.

[0049] Table 1. Performance of UV cross-linked water-based exposed roof waterproof coating

[0050] Example 2

[0051] A UV cross-linked water-based exposed roof waterproof coating, the components of which are as follows by weight: 5 parts of multifunctional additives, 10 parts of ammonium salt dispersants, 10 parts of film-forming additives, 2 parts of substrate wetting agents, 5 parts of mineral oil defoamers, 1 part of silicone defoamers, 5 parts of alkali swelling thickeners, 1 part of polyurethane thickeners, 400 parts of heavy calcium powder-coarse powder, 50 parts of heavy calcium powder-fine powder, 3 parts of titanium dioxide, 350 parts of acrylic elastic emulsions, 120 parts of styrene acrylic emulsions, and 125 parts of deionized water.

[0052] In the above-mentioned UV cross-linked water-based exposed roof waterproof coating, the selection of each raw material is basically the same as that in Example 1, except that the particle size of the heavy calcium powder-coarse powder is 400 mesh, and the particle size range of the heavy calcium powder-fine powder is 1250 mesh.

[0053] During the preparation, 1) 100 parts of deionized water, 5 parts of mineral oil defoamer, 5 parts of multifunctional additive, 10 parts of ammonium salt dispersant, 400 parts of heavy calcium powder-coarse powder, 50 parts of heavy calcium powder-fine powder, 3 parts of titanium dioxide and 150 parts of acrylic elastic emulsion are dispersed at high speed by a disperser at room temperature, mixed evenly, and a pre-reaction slurry 1 with a fineness of 30-40 microns is obtained.

[0054] 2) Add 120 parts of styrene-acrylic emulsion, 10 parts of film-forming aid, 2 parts of substrate wetting agent, 1 part of silicone defoamer and 200 parts of acrylic elastic emulsion to the pre-reaction slurry 1 obtained in step 1), and disperse and mix them evenly with a disperser at room temperature to obtain pre-reaction slurry 2.

[0055] 3) Premix 5 parts of alkali swelling thickener and 10 parts of deionized water, stir evenly and set aside, premix 1 part of polyurethane thickener and 15 parts of deionized water, stir evenly and set aside, add the premixed alkali swelling thickener and polyurethane thickener to the pre-reaction slurry 2 obtained in step 2) to obtain a UV cross-linked water-based roof exposed waterproof coating.

[0056] The performance of the UV-crosslinked water-based exposed roof waterproof coating prepared in this embodiment is basically the same as that of Example 1. Example 3

[0057] A UV cross-linked water-based exposed roof waterproof coating, the components of which are as follows by weight: 2 parts of a multifunctional auxiliary agent, 5 parts of an ammonium salt dispersant, 5 parts of a film-forming auxiliary agent, 6 parts of a substrate wetting agent, 2 parts of a mineral oil defoamer, 5 parts of an organosilicon defoamer, 1 part of an alkali swelling thickener, 5 parts of a polyurethane thickener, 300 parts of heavy calcium powder-coarse powder, 150 parts of heavy calcium powder-fine powder, 20 parts of titanium dioxide, 450 parts of an acrylic elastic emulsion, 80 parts of a styrene-acrylic emulsion, and 60 parts of deionized water.

[0058] In the above-mentioned UV cross-linked water-based exposed roof waterproof coating, the selection of each raw material is basically the same as that in Example 1, except that the particle size of the heavy calcium powder-coarse powder is 800 mesh, and the particle size range of the heavy calcium powder-fine powder is 1000 mesh.

[0059] During the preparation, 1) 55 parts of deionized water, 2 parts of mineral oil defoamer, 2 parts of multifunctional additive, 5 parts of ammonium salt dispersant, 300 parts of heavy calcium powder-coarse powder, 150 parts of heavy calcium powder-fine powder, 20 parts of titanium dioxide and 200 parts of acrylic elastic emulsion are dispersed at high speed by a disperser at room temperature, mixed evenly, and a pre-reaction slurry 1 with a fineness of 30-40 microns is obtained.

[0060] 2) Add 80 parts of styrene-acrylic emulsion, 5 parts of film-forming aid, 6 parts of substrate wetting agent, 5 parts of silicone defoamer and 250 parts of acrylic elastic emulsion to the pre-reaction slurry 1 obtained in step 1), and disperse and mix them evenly with a disperser at room temperature to obtain pre-reaction slurry 2.

[0061] 3) Premix 1 part of alkali swelling thickener and 2 parts of deionized water, stir evenly and set aside; premix 5 parts of polyurethane thickener and 3 parts of deionized water, stir evenly and set aside; add the premixed alkali swelling thickener and polyurethane thickener to the pre-reaction slurry 2 obtained in step 2) to obtain a UV cross-linked water-based roof exposed waterproof coating.

[0062] The performance of the UV-crosslinked water-based exposed roof waterproof coating prepared in this embodiment is basically the same as that of Example 1.

[0063] Comparative example 1.

[0064] This comparative example is basically the same as Example 1, except that the addition amount of the multifunctional auxiliary agent is 10 parts.

[0065] Comparative example 2.

[0066] This comparative example is basically the same as Example 1, except that the added amount of the multifunctional auxiliary agent is 0.1 part.

[0067] Comparative example 3.

[0068] This comparative example is basically the same as Example 1, except that the dispersant is replaced by sodium salt dispersant 5027.

[0069] Comparative example 4.

[0070] This comparative example is basically the same as Example 1, except that the addition amount of the heavy calcium powder fine powder is 300 parts.

[0071] Comparative Example 5.

[0072] This comparative example is basically the same as Example 1, except that the polyurethane thickener is completely replaced by an equal amount of an alkali swelling thickener.

[0073] Comparative Example 6.

[0074] This comparative example is basically the same as Example 1, except that the alkali swelling thickener is completely replaced by an equal amount of polyurethane thickener.

[0075] Comparative Example 7.

[0076] This comparative example is basically the same as Example 1, except that all the styrene acrylic emulsion is replaced by an equal amount of acrylic elastic emulsion.

[0077] Comparative analysis of performance tests.

[0078] The waterproof coating prepared in Comparative Example 1 has a short shelf life and has problems of poor stability and pungent odor; this may be caused by the increased alkalinity. The waterproof coating prepared in Comparative Example 2 is prone to mold and has a pungent odor; this may be because the pH value of the system is acidic and produces an acidic odor, and the pH value does not meet the requirements for inhibiting the growth of bacteria.

[0079] The waterproof performance of the waterproof coating prepared in Comparative Example 3 is significantly reduced, which is specifically manifested in that water seepage occurs on the back of the paper after a funnel-shaped water seepage test for 7 days. Figure 2 As shown, the waterproof coating prepared in Example 1 of the present invention does not seep water from the back of the paper when the funnel-shaped water seepage test is carried out on the paper for 7 days. Figure 1 In addition, when comparative example 3 was tested for water-impermeability, water permeability occurred after 168 hours of testing at 0.3 MPa. The specific reason may be that the sodium salt dispersant is anionic and can form hydrogen bonds with water molecules, thus showing high hydrophilicity, which reduces the waterproof performance of the waterproof coating.

[0080] In comparative example 4, after increasing the amount of heavy calcium powder-fine powder added, the coated paint film will have hollowing and delamination. This may be because the system is too dense, resulting in the water vapor on the base surface not evaporating and thus forming hollowing and delamination.

[0081] In addition, from Figure 3 and Figure 4 By comparison, after increasing the amount of heavy calcium powder-fine powder added, the trampling resistance of the waterproof coating also decreased significantly, and the road surface was trampled for two years and there was shedding and lifting; while the waterproof coating prepared in the embodiment of the present invention did not lift or fall off after being trampled on the road surface for two years.

[0082] Comparative Example 5 has the problem of too high viscosity leading to decreased self-leveling performance, while Comparative Example 6 has the problem of decreased viscosity leading to poor control of paint film thickness. These two comparative examples show that the alkali swelling thickener and the polyurethane thickener can work synergistically, both of which can increase the viscosity of the system, make it easier to control the thickness of the paint film during construction, and promote the leveling and self-leveling of the system during film formation.

[0083] The overall hardness of the paint sample of Comparative Example 7 is very high, and there are problems of decreased tensile strength, elongation at break, and low-temperature flexibility, specifically, the tensile strength is 0.22MPa, the elongation at break is 42%, and the low-temperature flexibility has cracks at -35°C.

[0084] It can be seen that the mixture of acrylic elastic emulsion and styrene acrylic emulsion can not only ensure the tensile strength, elongation at break, and low-temperature bendability of the system, and thus can still fill and penetrate into the cracks in the building, and even have the effect of heat insulation, but also ensure excellent bonding strength and water resistance under high elastic properties.

[0085] It should be noted that the above embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. The parts not described in the specific embodiments are all prior art or common knowledge.

Claims

1. A UV cross-linked water-based exposed roof waterproof coating, characterized in that: The components of the waterproof coating are as follows by weight: 1-5 parts of multifunctional additives, 5-10 parts of ammonium salt dispersants, 5-10 parts of film-forming additives, 2-6 parts of substrate wetting agents, 1-5 parts of mineral oil defoamers, 1-5 parts of silicone defoamers, 1-5 parts of alkali swelling thickeners, 1-5 parts of polyurethane thickeners, 300-400 parts of heavy calcium powder-coarse powder, 50-150 parts of heavy calcium powder-fine powder, 1-20 parts of titanium dioxide, 350-450 parts of acrylic elastic emulsion, 80-120 parts of styrene-acrylic emulsion, and 55-125 parts of deionized water; the particle size of the heavy calcium powder-coarse powder is 400-800 mesh, and the particle size range of the heavy calcium powder-fine powder is 1000-1250 mesh; the solid content of the acrylic elastic emulsion is 52±1%, and the viscosity is ≤500. mPa·s, glass transition temperature is -18℃, minimum film forming temperature is 0℃, density is 1.04 g / cm 3 ; The preparation steps of the above-mentioned UV cross-linked water-based exposed roof waterproof coating are as follows: 1) Place 50-100 parts of deionized water, 1-5 parts of mineral oil defoamer, 1-5 parts of multifunctional additive, 5-10 parts of ammonium salt dispersant, 100-150 parts of acrylic elastic emulsion, 300-400 parts of heavy calcium powder-coarse powder, 50-150 parts of heavy calcium powder-fine powder, and 1-20 parts of titanium dioxide in a disperser, disperse and mix them at a high speed of 1000-2000 r / min at room temperature to obtain a pre-reaction slurry 1 with a fineness of 30-40 microns; 2) Add 250-300 parts of acrylic elastic emulsion, 80-120 parts of styrene acrylic emulsion, 5-10 parts of film-forming aid, 2-6 parts of substrate wetting agent, and 1-5 parts of silicone defoamer to the pre-reaction slurry obtained in step 1), disperse and mix at a speed of 800-1200 r / min at room temperature to obtain pre-reaction slurry 2; 3) Premix 1-5 parts of alkali swelling thickener and 2-10 parts of deionized water and stir them evenly for later use; premix 1-5 parts of polyurethane thickener and 3-15 parts of deionized water and stir them evenly for later use; add the premixed alkali swelling thickener and polyurethane thickener to the pre-reaction slurry 2 obtained in step 2) to keep the viscosity of the whole system at 120-140ku, and obtain a UV cross-linked water-based exposed roof waterproof coating; When applying, use a roller to apply a layer of waterproof coating on a clean, flat, and hollow-free concrete or metal base. Wait for 4 to 12 hours until the surface is dry and not sticky, then check for hollowing, blistering, stratification, and poor curing. If these problems occur, repair them and then apply a second coat. The direction of the second coat is perpendicular to the direction of the first coat, and the thickness of each coat is controlled at 0.3mm-0.5mm.

2. A UV cross-linked water-based exposed roof waterproof coating according to claim 1, characterized in that: The multifunctional additive is a multifunctional additive of model AMP95 sold by Dow Chemical Investment Co., Ltd.

3. The UV cross-linked water-based exposed roof waterproof coating according to claim 1, characterized in that: The film-forming aid is a film-forming aid of model HB-285 sold by Foshan Abel Chemical Co., Ltd.

4. The UV cross-linked water-based exposed roof waterproof coating according to claim 1, characterized in that: The substrate wetting agent is a wetting agent of model SWA-1 sold by Dow Chemical Investment Co., Ltd.

5. The UV cross-linked water-based exposed roof waterproof coating according to claim 1, characterized in that: The mineral oil defoamer is a defoamer of model SX-NXZ2 sold by Yangzhou Sixin New Material Technology Co., Ltd., and the silicone defoamer is a defoamer of model SX-63A sold by Yangzhou Sixin New Material Technology Co., Ltd.

6. The UV cross-linked water-based exposed roof waterproof coating according to claim 1, characterized in that: The alkali swelling thickener is a thickener of model A401 sold by Wanhua Chemical Group Co., Ltd., and the polyurethane thickener is a thickener of model U604 sold by Wanhua Chemical Group Co., Ltd.

Citation Information

Patent Citations

  • Water-resistant elastic outer wall paint

    CN103992698A

  • Waterproof coating and preparation method and application thereof, and asphalt waterproof coiled material

    CN105368236A

  • Organic elastic pseudo-fair-faced concrete paint

    CN105130315A

  • Low-carbon environment-friendly high-performance elastic coating and preparation method thereof

    CN115851050A